Spatio-temporal variations of absorbing aerosols and their relationship with meteorology over four high altitude sites in glaciated region of Pakistan. (1st September 2019) - Nasir, Jawad; Zeb, Bahadar; Sorooshian, Armin; Mansha, Muhammad; Alam, Khan; Ahmad, Ifthikhar; Rizvi, Hussain Haider; Shafiq, Muhammad
Abstract: In high Asia, absorbing aerosols, particularly black carbon (BC) and dust, reportedly have strong effects on glaciers and the hydrological cycle. Knowledge about influence of BC over Hindukush-Karakoram-Himalaya (HKH) region in northern Pakistan is limited and therefore, required in-depth investigation. This study reports on the ground based BC and satellite based aerosol variations during the period 2016–2017, over four high altitude stations, including Astore, Gilgit, Sost, and Skardu, representing HKH range in northern Pakistan. Hourly, daily, and monthly variations of BC aerosol were examined in relation to meteorology. BC aerosols exhibited diurnal variations with sharp morning and evening peaks. During the study period BC concentrations were in the range of 0.9–6.1 μg/m 3 over the study locations. During the study period, the average BC concentration over Astore, Gilgit, Sost and Skardue were 2.6 ± 0.7, 3.7 ± 0.6, 2.1 ± 1.1 and 3.0 ± 1.0 μg/m 3, respectively. AOD varies from 0.01 to 0.16 and AI ranges from 0.2 to 5.5 during the study period. BC aerosols exhibited positive correlations with temperature and wind speed, in addition to a negative correlation with relative humidity. BC also has a positive correlation with AOD and AI. The long range transport of aerosols to the receptor sites were from central Asia, Eastern Europe, Middle East and India as well. Highlights: Daily and monthly variations in BC mass concentration were analyzed. Contrasting variations in BC, AOD and AI were observed during the study period. Hourly variations and day/night time ratio of BC concentration were investigated. BC mass concentration shows significant variations with meteorological parameters.